2021
DOI: 10.1177/11786388211035220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Regular Khat Chewing on Serum Fasting Sugar Level in Diabetic patients versus Healthy Individuals; A comparative study

Abstract: Background: Khat chewing is a long standing social-cultural habit in several countries. Even though many people chew khat simply for its pleasurable and stimulatory effect, evidence showed widely-held belief among khat chewers in Ethiopia and other part of the world that khat helps to lower blood glucose while some studies are contradicted on the effect of khat. There is limited data about khat’s effect on blood glucose especially in our setting, Harar estern Ethiopia. Objective: Primarily the present study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In the present meta-analysis, the pooled prevalence of good and poor glycemic control in Ethiopia was estimated using 46 articles. 19,24,25, 47 - 89 In a random effect model, the pooled prevalence of good glycemic control was found to be 38.08% (95% CI: 34.08, 42.08) with significant heterogeneity among the included articles ( I 2 = 96.57%, P < .001) ( Figure 2 ). The potential sources of higher heterogeneity were investigated further.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present meta-analysis, the pooled prevalence of good and poor glycemic control in Ethiopia was estimated using 46 articles. 19,24,25, 47 - 89 In a random effect model, the pooled prevalence of good glycemic control was found to be 38.08% (95% CI: 34.08, 42.08) with significant heterogeneity among the included articles ( I 2 = 96.57%, P < .001) ( Figure 2 ). The potential sources of higher heterogeneity were investigated further.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled prevalence of good glycemic control was calculated from 5918 of the 15 457 study population and poor glycemic control was calculated from 9539 of the 15 457 study population. The original articles’ sample sizes ranged from 100 24, 55 to 2554. 49 Likewise, articles published between 2012 and 2021 were included in this study.…”
Section: Resultsmentioning
confidence: 99%
“…For ages, people in the Arabian Peninsula and the Horn of Africa, particularly Ethiopia, have practiced khat chewing [ 59 , 60 ]. Even though there were a few contradicting observations while exploring the effects of khat on glucose metabolism and insulin secretion in the literature, it has been demonstrated to increase serum glucose level-hyperglycemia [ 61 , 62 , 63 , 64 , 65 , 66 ]. Chewing khat has a considerable unfavorable impact on glucose management in diabetes in Ethiopia, according to the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Khat also has a cytotoxic effect on pancreatic cells and insulin synthesis, affecting regulation of blood glucose ( 41 ). However, there were contradictory findings about its effect on glycemic control ( 40 , 42 ). Therefore, another study is suggested to determine the actual effects of khat on the blood glucose level.…”
Section: Discussionmentioning
confidence: 99%